2018
DOI: 10.2147/opth.s162999
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased levels of plasma tumor necrosis factor alpha with primary open-angle glaucoma

Abstract: PurposeRetinal ganglion cell (RGC) death is a key feature of glaucoma. Elevated levels of tumor necrosis factor alpha (TNF-α), a pro-inflammatory cytokine, can induce RGC apoptosis and play a critical role in glaucomatous neurodegeneration. Based on the possible role of inflammation and oxidative stress in the pathogenesis of primary open-angle glaucoma (POAG), we investigated the association between plasma levels of TNF-α and POAG or its clinical indices in comparison to non-glaucomatous controls.Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
4
19
2
6
Order By: Relevance
“…Other authors have speculated that an elevated neutrophil-to-lymphocyte ratio and the systemic immune inflammation index might serve as predictors for POAG [ 24 ]. Kondkar et al found high systemic level of the inflammatory cytokine TNF-α in their study of 51 POAG patients, compared to 88 controls [ 25 ]. Nonetheless, the mechanisms linking increased intraocular pressure to increased systemic inflammation have not been sufficiently elucidated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have speculated that an elevated neutrophil-to-lymphocyte ratio and the systemic immune inflammation index might serve as predictors for POAG [ 24 ]. Kondkar et al found high systemic level of the inflammatory cytokine TNF-α in their study of 51 POAG patients, compared to 88 controls [ 25 ]. Nonetheless, the mechanisms linking increased intraocular pressure to increased systemic inflammation have not been sufficiently elucidated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol derivatives have similar pharmacological effects to those of currently used glaucoma drugs and have potential for drug development as www.nature.com/scientificreports www.nature.com/scientificreports/ antiglaucoma agents. In the DGIdb, celecoxib, paclitaxel, and cyclosporine appeared frequently, suggesting that antineoplastic drugs may represent a new direction for glaucoma drug screening 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Это взаимодействие осуществляется посредством выработки различных цитокинов, хемокинов, нейротрофических факторов и других сигнальных молекул, которые участвуют в синтезе, деградации и модификации различных компонентов ЭЦМ трабекулярной сети [6]. В литературе приведены данные исследований, в которых оценивались концентрации цитокинов в биологических жидкостях и тканях у больных с различными формами глаукомы: сыворотке крови [23, 24,25,31], водянистой влаге (ВВ) [8,9,31,36], слезе [9,17], лизате клеток трабекулярной сети [27]. ПЭ синдром является фактором риска развития ПЭ глаукомы и представляет собой ассоциированное с возрастом системное нарушение фибриллогенеза, которое возникает в результате повышенного образования и неправильной сборки компонентов эластиновых микрофибрилл, что приводит к отложению в различных тканях аномального фибриллярного материала [11].…”
Section: Introductionunclassified